A bench‐top molding method for the production of cell‐laden fibrin micro‐fibers with longitudinal topography. Issue 4 (13th August 2019) - Keijdener, Hans; Konrad, Jens; Hoffmann, Bernd; Gerardo‐Nava, José; Rütten, Stephan; Merkel, Rudolf; Vázquez‐Jiménez, Jaime; Brook, Gary A.; Jockenhoevel, Stefan; Mela, Petra
Abstract: Tissue‐engineered constructs have great potential in many intervention strategies. In order for these constructs to function optimally, they should ideally mimic the cellular alignment and orientation found in the tissues to be treated. Here we present a simple and reproducible method for the production of cell‐laden pure fibrin micro‐fibers with longitudinal topography. The micro‐fibers were produced using a molding technique and longitudinal topography was induced by a single initial stretch. Using this method, fibers up to 1 m in length and with diameters of 0.2–3 mm could be produced. The micro‐fibers were generated with embedded endothelial cells, smooth muscle cell/fibroblasts or Schwann cells. Polarized light and scanning electron microscopy imaging showed that the initial stretch was sufficient to induce longitudinal topography in the fibrin gel. Cells in the unstretched control micro‐fibers elongated randomly in both the floating and encapsulated environments, whereas the cells in the stretched micro‐fibers responded to the introduced topography by adopting a similar orientation. Proof of concept bottom‐up tissue engineering (TE) constructs are shown, all displaying various anisotropic organization of cells within. This simple, economical, versatile and scalable approach for the production of highly orientated and cell‐laden micro‐fibers is easily transferrable to any TE laboratory.